Citra Majapahit dalam Perbandingan Babad dan Kakawin - Bambang Soelistyanto (Berkala Arkeologi, 1994)
Experts have assumed that among the many ancient kingdoms in Indonesia, Majapahit is the strongest to leave memories in today's society. The last kingdom of this traditional Hindu-Javanese state was recorded as having fully succeeded in establishing political unity in a large area that had never happened before.